Fuzzy SAW Based Decision Model for Determining the Priority Scale of ICT Handling in Public Sector Organizations - Yulanda, Rissa; Utama, Ditdit Nugeraha (Journal of Applied Data Sciences, 2024)
Determining the priority of handling information and communication technology (ICT) infrastructure in public sector organizations can help them take the right actions in maximizing limited budgets, to handle technical maintenance, improve human resource (HR) capabilities and governance of ICT infrastructure. The purpose of this research is to develop a decision-making model that is able to determine the priority of handling ICT, especially in public sector organizations. Decision support modeling (DSM) with Fuzzy Simple Additive Weighting (Fuzzy SAW) method is used to build a computer model that supports decision making in this case. The study consists of four stages, which are an integral part of the Fuzzy SAW-based DSM process. These stages include analyzing the case, determining parameters, collecting data and building the model. This study produces a Fuzzy SAW-based DSM consisting of 14 parameters, namely governance, number of internet users, number of ICT managers, work experience of ICT managers, bandwidth service capacity, router device age, educational background of ICT managers, network firewalls, network maintenance, server room availability, Network Attached Storage (NAS) storage devices, neatly organized cable devices, adequate electrical resources and internet connection backup networks, to determine the priority ranking of 34 existing alternatives. The final result of this research is a Fuzzy SAW-based DSM that is able to provide a priority score for handling ICT infrastructure in Public Sector Organizations. The findings in this model show that the parameter weights affect the final score of the model. Thus, the conclusion of this research is that the model has been successfully implemented, making a significant contribution in providing guidance on determining accurate ICT infrastructure handling for public sector organizations.